Between food fulfillment and income: Can urban agriculture contribute to both? - Oekan S. Abdoellah; Yusep Suparman; Kinanti Indah Safitri; Akhmad Zainal Mubarak; Mira Milani; Margareth; Levaldo Surya (Geography and Sustainability, 2023)
Food and Agriculture Organization (FAO) is appealing for a global implementation of urban agricultural strategies to increase food availability. Bandung, a city in Indonesia, is already participating in this initiative. This research aimed to assess the contribution of urban agriculture toward household food fulfillment and income. Furthermore, the impacts on urban, subsistence, semi-commercial, and commercial agriculture were considered. In-depth interviews to obtain qualitative data and observations were also utilized. A survey of 321 households, consisting of 107 for each urban agricultural type, used questionnaires to obtain quantitative data. These inputs were further analyzed to determine the contribution of household food fulfillment and income. The results showed that average urban agriculture has an insignificant and significant contribution of 9% and 41.5% to household food fulfillment and income. This was due to the vast complexities of metropolitan problems, including limited access to land, lack of participation, dependence on on-market products, and increasing commercialization which opposed urban agricultural policies.